2014
DOI: 10.3855/jidc.4236
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of infections caused by Stenotrophomonas maltophilia in a hospital in northwest China

Abstract: Introduction: Stenotrophomonas maltophilia infections have recently increased in importance in China, particularly in intensive care units (ICUs). The aim of this study was to investigate the clinical characteristics and risk factors of S. maltophilia infection in ICU of a hospital in northwest China. Methodology: The characteristics and outcomes of patients with any type of S. maltophilia infection at Shaanxi Provincial People's Hospital, Shaanxi, China, over a two-year period (from July 2011 to June 2013) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
2
22
2
Order By: Relevance
“…In contrast, Sattler et al17 found that prematurity, primary immunodeficiency, and congenital heart disease were unique and more common risk factors among pediatric patients in their study. In contrast with many previous studies, exposure to antibiotics in this study was found in both infected and colonized patients 13,14,22,26. Carbapenems are among the classes of antibiotics most frequently associated with S. maltophilia isolation 26.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…In contrast, Sattler et al17 found that prematurity, primary immunodeficiency, and congenital heart disease were unique and more common risk factors among pediatric patients in their study. In contrast with many previous studies, exposure to antibiotics in this study was found in both infected and colonized patients 13,14,22,26. Carbapenems are among the classes of antibiotics most frequently associated with S. maltophilia isolation 26.…”
Section: Discussioncontrasting
confidence: 96%
“…Respiratory tract infection, especially VAP, and BSI are the most common infections reported in many clinical and epidemiological studies. The spectrum of the clinical diseases caused by S. maltophilia in this study was similar to that observed in other relevant studies 3,5,11-13…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations